The Influence of Distractors on Saccade-Target Selection: Saccade Trajectory Effects - Robin Walker; Eugene McSorley (Journal of Eye Movement Research)
It has long been known that the path (trajectory) taken by the eye to land on a target is rarely straight (Yarbus, 1967). Furthermore, the magnitude and direction of this natural tendency for curvature can be modulated by the presence of a competing distractor stimulus presented along with the saccade target. The distractor-related modulation of saccade trajectories provides a subtle measure of the underlying competitive processes involved in saccade target selection. Here we review some of our own studies into the effects distractors have on saccade trajectories, which can be regarded as a way of probing the competitive balance between target and distractor salience.